2018
DOI: 10.1016/j.abrep.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Online activities, prevalence of Internet addiction and risk factors related to family and school among adolescents in China

Abstract: AimsTo investigate the online activities, prevalence of Internet Addiction in relation to demographic characteristics and risk factors related to family and school among adolescents.MethodsA total of 6468 10–18 year old adolescents recruited from local schools in Guangzhou, China were selected by adopting multi-stage stratified random sampling (female/male: 2886/3582; mean age:13.78 ± 2.43). Participants completed a structured questionnaire.ResultsThe overall prevalence of Internet Addiction was 26.50%, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
153
3
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(213 citation statements)
references
References 39 publications
21
153
3
16
Order By: Relevance
“…They used internet for school/work (20.2%) and entertainment (11.9%). [31] Other study done by Miao (2017) [32] found that Social networking, school work, entertainment, gaming and shopping ranked as the top five among all the online activities. According to literature, values used as reference points to characterize long electronic devices use time varies between 2 and 5 hours/day.…”
Section: Discussionmentioning
confidence: 99%
“…They used internet for school/work (20.2%) and entertainment (11.9%). [31] Other study done by Miao (2017) [32] found that Social networking, school work, entertainment, gaming and shopping ranked as the top five among all the online activities. According to literature, values used as reference points to characterize long electronic devices use time varies between 2 and 5 hours/day.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in a study done by Xin in China, where common online activities were social networking (94.73%), school work (86.53%), entertainment (82.44%), internet gaming (73.42%) and shopping online (33.67%). 2 In the current study the prevalence of mild internet addictive behaviour causing occasional or frequent problems was found in 55.8% and severe addictive behaviour causing significant problem in life in 0.1% of students. In a study done by Xin, the overall prevalence of Internet Addiction was low (26.50%), compared to our study but severe addiction was 0.96% which is higher.…”
Section: Discussionmentioning
confidence: 45%
“…In a study done by Xin, the overall prevalence of Internet Addiction was low (26.50%), compared to our study but severe addiction was 0.96% which is higher. 2 A prevalence of 25.1% of problematic internet use is found in a study done by Vries et al among adult psychiatric patients. 3 Another study done by Goswami in central India, showed that 32.9% of students were having mild internet addiction, 16.3% moderate and 0.4% severe internet addiction.…”
Section: Discussionmentioning
confidence: 93%
“…Study by Xin M et al [16] among 6468 adolescents in China showed a 26.50% prevalence of Addictive internet use overall and 0.96% severe addiction. Addictive internet use was found to be more among males (30.6%) than females (21.2%).…”
Section: Discussionmentioning
confidence: 97%